Preparing preservice EFL teachers for CALL normalisation: A technology acceptance perspective. (July 2019) - Mei, Bing
Abstract: This study aims to provide a practical framework to measure the effect of current English as a foreign language (EFL) teacher education programmes on preparing preservice teachers for computer-assisted language learning (CALL) normalisation. To this end, the study compared the attitudinal and cognitive differences between preservice teachers at the junior and senior levels. Guided by prior technology acceptance research, a research model consisting of six relevant dimensions was proposed. Preservice EFL teachers from a Chinese university were invited to respond to an online questionnaire and the resultant data were analysed through structural equation modelling. Following confirmatory factor analysis, participants were divided into two groups according to their year level. Measurement invariance was checked first and then latent mean differences between the junior group ( n = 204) and the senior group ( n = 91) were compared. Measurement invariance results suggest that there existed measurement invariance across groups. Meanwhile, for the latent mean difference test, only one significant mean difference was detected in perceived usefulness, with the senior group showing a higher mean score. The findings demonstrate that though progress has been made, the programme may need further improvement. Implications for teacher educators, institutional leaders, and policymakers are also discussed.